نحو صناديق استثمار اجتماعية تخدم التنمية الاقتصادية في ضوء نظام الاستثمار الإسلامي: TOWARDS SOCIAL INVESTMENT FUNDS SERVING ECONOMIC DEVELOPMENT IN LIGHT OF ISLAMIC INVESTMENT PRINCIPLES - Mohammed Hashem, Osamah Yahya (I-iECONS e-proceedings, 2023)
تهدف هذه الدراسة إلى إبراز الدور الاجتماعي الذي يمكن أن تلعبه صناديق الاستثمار الإسلامية، وتفنيد النظرة التقليدية حول هذه الصناعة، من كونها مؤسسات مالية وسيطة إلى مؤسسات تسعى لخدمة المجتمعات ورفاهيتها والمساهمة الفاعلة في تنميتها، وأن هناك ثمة طرق وأساليب ممكنة في سبيل تعزيز الدور الاجتماعي لصناديق الاستثمار الإسلامية، كما تسعى الدراسة إلى إبراز بعض الخصائص التي تتميز بها صناديق الاستثمار الاجتماعية، فهي مع تعظيمها للربحية التجارية، تسعى لتنمية المجتمعات الاسلامية، كونها أداة من أدوات الاستثمار الإسلامي، تخضع لجميع مبادئه وأحكامه ومقاصده، وقد توصلت الدراسة إلى عدة نتائج من أهمها: أن صناديق الاستثمار الاجتماعية يمكن أن تستهدف السوقين الأولية والثانوية، ولا تقتصر عملياتها على الثانوية وحسب، كما أنها تخضع في مبادئها وعملياتها لمقاصد الاستثمار الإسلامي، وتعد من أكثر الأدوات الاستثمارية امتثالاً للمسؤولية الاجتماعية، كما توصلت إلى بعض الصناديق الاجتماعية المبتكرة التي يمكن أن تولد أكبر نفع للأفراد والمجتمعات، وقد اقترح الدراسة بعض الصناديق الاجتماعية، وكلها تخدم قطاعين من أهم القطاعات التنموية المجتمعية، وهما القطاع الخدمي والقطاع الإنتاجي. ولأن الدور التنموي لا يكتمل إلا بالتقييم الناجح الذي يهدف لتعزيز الأداء وتعظيم الأثر، فقد اقترحت الدراسة بعض المعايير التي يمكن أن تساهم في قياس وتقييم الأداء التنموي والأثر الاجتماعي لتلك الصناديق. This study aims to highlight the social role that Islamic investment funds can play, dispelling the traditional view of this industry as mere financial intermediaries to institutions that seek to serve communities, enhance their well-being, and actively contribute to their development. The study also explores potential ways and methods to enhance the social role of Islamic investment funds. While maximizing profitability, these funds aim to foster Islamic communities as an integral part of Islamic investment principles, adhering to all its principles, rules, and objectives. The study has yielded several important results, including the potential for social investment funds to target both primary and secondary markets, and not limited to the latter. These funds operate according to Islamic investment principles and are among the most socially responsible investment tools. The study has identified some innovative social funds that can generate significant benefits for individuals and communities. It proposes several such funds, all of which serve two of the most critical community development sectors: the service sector and the productive sector. Recognizing that the developmental role is incomplete without successful evaluation aimed at enhancing performance and maximizing impact, the study suggests criteria for measuring and assessing the developmental performance and social impact of these funds.